2018
DOI: 10.1002/qj.3292
|View full text |Cite
|
Sign up to set email alerts
|

An improved moist‐convective rotating shallow‐water model and its application to instabilities of hurricane‐like vortices

Abstract: We show how the two-layer moist-convective rotating shallow-water model (mcRSW), which proved to be a simple and robust tool for studying effects of moist convection for large-scale atmospheric motions, can be improved. The improvement is achieved by including, in addition to the water vapour, precipitable water, and the effects of vaporization, entrainment, and precipitation, rendering the model cloud-resolving. It is applied, as an illustration, to model the development of instabilities of tropical cyclone-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
(54 reference statements)
1
20
0
Order By: Relevance
“…They showed that the equatorial modons keep their coherence in the moist-convective environment. Moreover, as is known, and confirmed in mcRSW [19,20], condensation leads to intensification of the cyclonic vortices. Correspondingly, the potential vorticity (PV) anomalies become stronger, the size smaller, and the phase speed of the convectively-coupled modon becomes higher than that of its adiabatic counterpart.…”
supporting
confidence: 58%
“…They showed that the equatorial modons keep their coherence in the moist-convective environment. Moreover, as is known, and confirmed in mcRSW [19,20], condensation leads to intensification of the cyclonic vortices. Correspondingly, the potential vorticity (PV) anomalies become stronger, the size smaller, and the phase speed of the convectively-coupled modon becomes higher than that of its adiabatic counterpart.…”
supporting
confidence: 58%
“…g = g(θ/θ 0 ) is effective gravity defined by the mean potential temperature of the atmospheric layer θ normalised by a reference value θ 0 , and f is the Coriolis parameter, h is the thickness of the layer defined as pseudo-height (note that the atmospheric shallow water model is "upside-down", in a sense that the free surface is on the ground and the fixed pseudo-height (pressure) level is on the top, while geopotential is constant on the ground, cf. (Bouchut et al, 2009;Rostami and Zeitlin, 2018),…”
Section: DVmentioning
confidence: 99%
“…where M = h − γq is an analog of a moist static energy or moist enthalpy for the system. The above moist shallow water (MSW) equations are similar to those used by Bouchut et al (2009) and Rostami & Zeitlin (2018), although the implementation and the experiments, described below, significantly differ. Evaporation from a wet surface is parameterized by a bulk-aerodynamic-type formula,…”
Section: The Moist Shallow Water Equationsmentioning
confidence: 99%